Reconstructing the Role of BAZNAS in Socioeconomic Community Empowerment through the Housing Rehabilitation Program in Trenggalek - Azizah, Siti Irmi Nur; Roisatunnisa’, Faiza; Lutfiana, Silvi; Faiza, Nurlaili Adkhi Rizfa (Journal of Community Engagement in Economics, 2024)
The house renovation program is one of the community empowerment efforts that aims to improve the welfare of underprivileged families through proper housing repairs. BAZNAS Trenggalek plays an active role in this program by providing assistance and mentoring to beneficiaries. This research uses a community service method with a participatory approach, where the mentoring process is carried out in a structured manner, starting from the stages of needs identification, planning, implementation, to program evaluation. The results of the service show that community involvement in the house renovation process not only improves the quality of housing, but also strengthens collective awareness and independence in maintaining and improving their living conditions. In addition, this program provides positive social and economic impacts for beneficiaries. Thus, the assistance provided by BAZNAS Trenggalek contributes significantly to creating sustainable social change in the community